Promoting Gender Equality in Employment Through Resources Generated by Public and Private Entities in Spain - Olmo Gascón, Ana Marta (DIXI, 2014)
The process of developing and managing equality plans in companies and government is extremely complex, and in recent years various public entities, the most representative trade unions and women’s attorneys’ organizations have written valuable documents, indicating the procedure and the most appropriate contents for guaranteeing the principle of equal treatment on the grounds of gender in employment. Ths work, which has gone somewhat unnoticed, is reviewed in the following pages, in which studies by trade unions are also analyzed to review the measures contained in collective bargaining and equality plans in our country, highlighting those that can be considered as good practice in the workplace to equate women and men.